Research of a combined power and cooling system based on fuel rotating cooling air turbine and organic Rankine cycle on hypersonic aircraft. (15th December 2019) - Sun, Hongchuang; Qin, Jiang; Li, Haowei; Huang, Hongyan; Yan, Peigang
Abstract: Sustained power supply and thermal protection of electronic elements are two essential problems for developing long-endurance and reusable hypersonic aircrafts. In this study, a combined power and cooling (CPC) system is established between high temperature incoming air and low temperature fuel based on fuel cooling air turbine and organic Rankine cycle (ORC). The organic Rankine cycle is investigated based on thermodynamic analysis. The fuel rotating cooling air turbine is modeled with a mean diameter of 150 mm and investigated with 3D CFD simulation. The turbulence models for main flow and cooling channel are k-omega and SST, respectively. And the CFD method for air turbine is verified with land experimental test. Finally, the performance of the CPC system is theoretically researched. ORC can obviously increase the power output of the CPC system. With the designed air turbine, the real power output of the CPC system is 118.5 kW, higher by 20.7% than air turbine's power of 98.2 kW. The obtained mass flow rate of cooling air is 0.292 kg/s. The blade of the air turbine can be cooled with reasonable low mass flow rate of 5 g/s per blade. Highlights: The power of the CPC system is 118.5 kW, including AT 98.2 kW and ORC 20.3 kW. Fuel with 5 g/s per blade is enough for cooling the air turbine. The mass flow of cooling air obtained after ORC is 0.292 kg/s. Air turbine land experimental test is carried out.